2006
DOI: 10.1248/yakushi.126.1117
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Mechanism of Food Factors in Bone Metabolism and Prevention of Osteoporosis

Abstract: Aging induces a decrease in bone mass, and osteoporosis with its accompanying decrease in bone mass is widely recognized as a major public health problem. Bone loss with increasing age may be due to decreased bone formation and increased bone resorption. Pharmacologic and nutritional factors may prevent bone loss with aging, although chemical compounds in food and plants which act on bone metabolism are poorly understood. We have found that iso‰avones (including genistein and daidzein), which are contained in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(18 citation statements)
references
References 119 publications
0
16
0
2
Order By: Relevance
“…Several studies have demonstrated that flavonoids stimulate bone metabolism to improve bone mineral density [20, 21]. Hesperetin, a member of the flavanone subclass of flavonoids, is found mainly in citrus fruits.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that flavonoids stimulate bone metabolism to improve bone mineral density [20, 21]. Hesperetin, a member of the flavanone subclass of flavonoids, is found mainly in citrus fruits.…”
Section: Discussionmentioning
confidence: 99%
“…The lifetime risk of having at least one fracture is reduced by 25% with the daily use of 800 IU vitamin D, 45  μ gm vitamin K2, and 1200 mg calcium [10]. Vitamin K2 (MK-7) from fermented soybeans stimulates osteoblasts and inhibits osteoclasts resulting in an anabolic effect on bone calcification [11]. A systematic review (level of evidence I [LOE = A]) has shown vitamin K2 to prevent fractures in vertebra by 60%, hip fractures by 77%, and nonvertebral fractures by 81% in Japanese patients [12].…”
Section: Vitamin K and Osteoporosismentioning
confidence: 99%
“…Thus, the risk of osteoporosis is increased in postmenopausal women because of their reduced estrogen production. Soy isoflavone, which has similar but weak effects to estrogen, is known to regulate bone metabolism (Yamaguchi 2006). It has been reported that osteoporosis may be prevented by the ingestion of Ca and soy isoflavone (Wong et al 2009;Alekel et al 2010;Verbrugge et al 2012), but they are insufficient to prevent osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, if the bone metabolism can be maintained and/or the bone mass increased via the oral intake of LPSp, it may be possible to utilize LPSp as a novel mechanism for osteoporosis prevention. The mechanism of action of LPSp is probably different from that of isoflavone, because isoflavones regulate bone metabolism by binding to estrogen receptors similar to estrogen (Yamaguchi 2006). Therefore, there may be a synergistic effect between LPSp and isoflavone.…”
Section: Introductionmentioning
confidence: 99%